(untitled) (PJDOL, 2023)
Present study focuses on examining the nature of supervision often unreported by the career-oriented, educated and passionate individuals in banking profession. The objective of the present study is to empirically validate the differences (if any) between working and educated class, and to probe into the gender-sensitivity and nature of household (i.e. traditional career couples vs. dual career couples). Literature evidence is suggestive that added family responsibilities (in terms of being parents) reduce decisiveness about career–switching, often resulting in an unending exposure to abusive supervision.